Predicting Winter Ammonia and Methane Emissions from a Naturally Ventilated Dairy Barn in a Cold Region Using an Adaptive Neural Fuzzy Inference System - Hualong Liu; Xin Wang; Tana; Tiezhu Xie; Hurichabilige; Qi Zhen; Wensheng Li (Agriculture, 2025)
This study aims to characterize the emissions of ammonia (NH3) and methane (CH4) from naturally ventilated dairy barns located in cold regions during the winter season, thereby providing a scientific basis for optimizing dairy barn environmental management. The target barn was selected at a commercial dairy farm in Ulanchab, Inner Mongolia, China. Environmental factors, including temperature, humidity, wind speed, and concentrations of NH3, CH4, and CO2, were monitored both inside and outside the barn. The ventilation rate and emission rate were calculated using the CO2 mass balance method. Additionally, NH3 and CH4 emission prediction models were developed using the adaptive neural fuzzy inference system (ANFIS). Correlation analyses were conducted to clarify the intrinsic links between environmental factors and NH3 and CH4 emissions, as well as the degree of influence of each factor on gas emissions. The ANFIS model with a Gaussian membership function (gaussmf) achieved the highest performance in predicting NH3 emissions (R2 = 0.9270), while the model with a trapezoidal membership function (trapmf) was most accurate for CH4 emissions (R2 = 0.8977). The improved ANFIS model outperformed common models, such as multilayer perceptron (MLP) and radial basis function (RBF). This study revealed the significant effects of environmental factors on NH3 and CH4 emissions from dairy barns in cold regions and provided reliable data support and intelligent prediction methods for realizing the precise control of gas emissions.